Role of ozone therapy in the treatment of hypertensive ischemic heart disease. Review and case presentation (Ozone Therapy Global Journal, 2024)
Cardiovascular diseases continue to be the leading cause of death in most Western countries. According to the World Health Organization, ischemic heart disease generally refers to conditions involving narrowing or blockage of blood vessels, caused by damage to the heart or blood vessels by atherosclerosis.The present case presents hypertensive ischemic heart disease with a background of Diabetes Mellitus 2, uncontrolled dyslipidemia and obesity.Since ozone therapy can activate the antioxidant system, improve blood circulation and oxygen supply to tissues, the patient was treated from the beginning with Ozonated Saline Solution (SSO3) under micro bubbling, for 5 consecutive days with the aim of stabilizing the patient as soon as possible and establishing the therapeutic efficacy of ozone combined with antithrombotic and antihypertensive therapy.The patient debuted with chest pain, intense front-occipital headache and significant dyspnea. He was admitted to intensive care where, by means of an angio-CT and echocardiography, he was diagnosed with ischemic and hypertensive heart disease, concentric hypertrophy of the left ventricle, mitral aortic sclerosis and calcification, and hypokinesia of the distal third of the septum and tip.The patient responded favorably to the combined therapy, and was transferred to the ward after 48 hours with oxygen support saturating normally. There he continued with his treatment for 15 days. He was discharged after 15 days of hospitalization under strict outpatient treatment and medical follow-up.It was established that the Ozonated Saline Solution under micro bubbling as a complement to the basic therapy was safe and effective in this patient..